2020
DOI: 10.1088/1402-4896/abbe51
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of effect of electron temperature on intensity and efficiency of terahertz generated by laser beating in inhomogeneous plasma

Abstract: We report terahertz (THz) wave generation based on mixing of two radially polarized hollow Gaussian laser beams in periodic density plasma. We incorporate the effect of plasma electron temperature on THz intensity and efficiency. Our investigations reveal that emitted THz is radially polarized. Brightness and efficiency of THz significantly increase with plasma electron temperature. Our scheme predicts upto 2.4-fold enhancement in THz conversion efficiency with increase in plasma electron temperature from 0–10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Zhang et al [77] did two-dimensional particle-in-cell simulations of ultra-intense relativistic laser plasma interaction of solid target to generate the terahertz pulses by coherent transition radiation and THz radiation energy increased by 10 times. Manendra et al [78] investigated the effect of electron temperature on intensity and efficiency of terahertz generated by laser beating in inhomogeneous plasma [79]. Manendra et al [78][79][80] used radially polarized lasers having a top-hat envelope profile [s (profile index) ≥ 1] in density modulated hot plasma and concluded that the conversion efficiency increased by 5 times, at the electron thermal velocity 0.2c, where c is speed of light.…”
Section: Beat Wave Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [77] did two-dimensional particle-in-cell simulations of ultra-intense relativistic laser plasma interaction of solid target to generate the terahertz pulses by coherent transition radiation and THz radiation energy increased by 10 times. Manendra et al [78] investigated the effect of electron temperature on intensity and efficiency of terahertz generated by laser beating in inhomogeneous plasma [79]. Manendra et al [78][79][80] used radially polarized lasers having a top-hat envelope profile [s (profile index) ≥ 1] in density modulated hot plasma and concluded that the conversion efficiency increased by 5 times, at the electron thermal velocity 0.2c, where c is speed of light.…”
Section: Beat Wave Schemesmentioning
confidence: 99%
“…Manendra et al [78] investigated the effect of electron temperature on intensity and efficiency of terahertz generated by laser beating in inhomogeneous plasma [79]. Manendra et al [78][79][80] used radially polarized lasers having a top-hat envelope profile [s (profile index) ≥ 1] in density modulated hot plasma and concluded that the conversion efficiency increased by 5 times, at the electron thermal velocity 0.2c, where c is speed of light. Liu et al [81] did two-dimensional particle-in-cell simulations to study the terahertz wave propagating in the stagnation region of a reentry plasma sheath and these investigations are useful to study the attenuation of radio waves in atmosphere communication.…”
Section: Beat Wave Schemesmentioning
confidence: 99%
“…Polarization singularities in coherent optical fields are the points at which any of the parameters that define the state of polarization of light is indeterminate, it could be used in free-space optical communication, high-resolution microscopy and strong focusing [10][11][12].Radially polarized (RP) beam and azimuthally polarized (AP) beam are two typical kind of cylindrical vector beams that the polarization direction is along the radial direction or vertical to the radial direction and are the classic polarization vortices beam. This peculiar non-uniformed polarized constructure make RP and AP beams have been investigated in detail and found many applications, such as free-space communication, microscopy, laser machining and optical data storage [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%